Cloning a plant amino acid transporter by functional complementation of a yeast amino acid transport mutant. - Hsu, L C (1993)
Amino acids are transported across the plasma membrane of plant cells by proton-amino acid symports. We report here the successful cloning of a neutral amino acid carrier by functional complementation. A histidine transport deletion mutant of Saccharomyces cerevisiae was transformed with an Arabidopsis thaliana cDNA library constructed in a yeast expression vector. Forty transformants, out of 10(5), allowed growth on a histidine-limiting medium. The acquired ability to grow on low histidine was shown to be strictly dependent on the protein encoded by the expression plasmid. Histidine and alanine transport activity were 10- to 20-fold greater in the transformants. The transport kinetics, inhibitor sensitivity, and substrate specificity match those of neutral system II, a neutral amino acid carrier we previously described in plasma membrane vesicles isolated from leaf tissue. The cDNA insert is 1.7 kb with an open reading frame that codes for a protein containing 486 amino acids with a calculated molecular mass of 52.9 kDa and three sites of potential N-linked glycosylation. Hydropathy analysis of the deduced amino acid sequence suggests this is an integral membrane protein with 10-12 membrane-spanning alpha-helices. Overall, the sequence of this amino acid carrier is not closely related to any other protein sequences in the GenBank data base. Interestingly, however, there are small regions of sequence that exhibit significant levels of similarity with at least seven other integral membrane proteins.